On the use of the doctrine of laissez faire, in investigating the economic resources of Ireland - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1849)
The natural resources of Ireland have furnished a favourite topic to Irish writers for the indulgence of national vanity; and the language of exaggeration has been too often applied in describing their extent and value. The stern realities of wide-spread distress have led others to contrast the misery with the alleged abundance, and thence to deduce unfavourable conclusions as to the character of the population. It would be quite foreign to my present purpose to examine how far the common estimate of these resources is founded on an accurate calculation of their market value. But amid this boasting and crimination, it is overlooked that natural resources, however lavishly bestowed, are valueless as instruments for the production of wealth, unless the arrangements respecting their use are based on sound economic principles.
Read December 21st 1847
Keywords: Laissez faire; Potato famine; 314.15